A Novel Approach to Improve the Quasi-Yagi Antenna Perfomances by Using an Ends-Fed Dipole Driver - Dmitriy A. Buhtiyarov; Anatoly P. Gorbachev; Svetlana Yu. Zhelezko (Newest Updates in Physical Science Research Vol. 6, 2021)
We present a novel method for improving the performance of quasi-Yagi antennas by employing the so-called ends-fed dipole radiator. A cylindrical prototype operating at 790 MHz is developed and tested to demonstrate this concept. The proposed radiator is a good candidate for producing high polarisation purity radiation because the area around the radiating arms is free of any conductors.The measured results show that such a driver can achieve an effective area reduction of up to 20% while improving the front-to-back ratio up to 17 dB without reducing bandwidth.